A study on the relationships between selected economic variables towards the interest rates case study: Malaysia / Uzir Shah Md Yusos - Md Yusos, Uzir Shah (2011)
Many studies have been conducted to determine the relationships between the economic variables and interest rates. This study were conducted in order to measure the applicability of all previous studies statement regarding the relationships of selected economic variables (gross domestic product, inflation and money supply) towards the interest rates in Malaysia. This study also conducted to understand the movement of all the variables over the 10 years period from 2001 to 2010. All data were collected on quarterly basis. Methods in measuring findings were single linear regression and multiple linear regressions. According to the findings, in Malaysia, only inflation rates show significance relationships towards the interest rates and the relationships are positives. This means that if Malaysian inflation rates rise, the interest rates will also rises. Gross domestic product and money supply (M2) result shows that there are no significant effect between them towards the interest rates in Malaysia. Conclusion from this study is, even they have been few study conducted in overseas shows that each independent variables in this study have significant effect towards the interest rates, but it seems that in Malaysia, only inflation rates have significant relationships toward the interest rates.